Beetles (Coleoptera) of Peru: A Survey of the Families. Pythidae Solier, 1834 - Pollock, Darren A. (2018)
The diversity of the family Pythidae (Coleoptera) is summarized for Peru. One genus (Ischyomius Chevrolat) and two species are recorded. Comments are given on classification and distribution of the family, as well as known biology and natural history, the latter based primarily on larval stages. Based on label data from previously examined specimens and from newly collected material, species of Ischyomius appear to be closely associated with several monocot plant families within order Zingerberales. Ischyomius singularis Chevrolat is recorded from Huánuco and Lima, while I. bicolor Champion is known from Loreto and Madre de Dios; specific collection localities are given.